Mitophagy associated self-degradation of phosphorylated MAP4 guarantees the migration and proliferation responses of keratinocytes to hypoxia - Yanhai Feng; Lingfei Li; Qiong Zhang; Yongqing He; Yao Huang; Junhui Zhang; Dongxia Zhang; Yuesheng Huang; Xia Lei; Jiongyu Hu; Gaoxing Luo (Cell Death Discovery, 2023)
Abstract Our previous study has announced that phosphorylated microtubule-associated protein 4 (p-MAP4) accelerated keratinocytes migration and proliferation under hypoxia through depolymerizing microtubules. However, p-MAP4 should exhibit inhibitory effects on wound healing, for it also impaired mitochondria. Thus, figuring out the outcome of p-MAP4 after it impaired mitochondria and how the outcome influenced wound healing were far-reaching significance. Herein, the results revealed that p-MAP4 might undergo self-degradation through autophagy in hypoxic keratinocytes. Next, p-MAP4 activated mitophagy which was unobstructed and was also the principal pathway of its self-degradation triggered by hypoxia. Moreover, both Bcl-2 homology 3 (BH3) and LC3 interacting region (LIR) domains had been verified in MAP4, and they endowed MAP4 with the capability to synchronously function as a mitophagy initiator and a mitophagy substrate receptor. And, mutating any one of them ruined hypoxia-induced self-degradation of p-MAP4, resulting in destroyed proliferation and migration responses of keratinocytes to hypoxia. Our findings unviewed that p-MAP4 experienced mitophagy-associated self-degradation through utilizing its BH3 and LIR domains under hypoxia. As a result, the mitophagy-associated self-degradation of p-MAP4 guaranteed the migration and proliferation responses of keratinocytes to hypoxia. Together, this research provided a bran-new pattern of proteins in regulating wound healing, and offered a new direction for intervening wound healing.